2022
DOI: 10.7717/peerj.13780
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear energy transition and CO2 emissions nexus in 28 nuclear electricity-producing countries with different income levels

Abstract: Background Nuclear energy carries the least environmental effects compared to fossil fuels and most other renewable energy sources. Therefore, nuclear energy transition (NET) would reduce pollution emissions. The present study investigates the role of the NET on CO2 emissions and tests the environmental Kuznets curve (EKC) in the 28 nuclear electricity-producing countries from 1996–2019. Methods Along with a focus on the whole panel, countries are divided into three income groups using the World Bank classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…Notably, the extent of the magnitude is 0.065 for the 14 EU countries. It, therefore, means that remarkable growth could be achieved in the development of the geothermal energy supply among the 14 EU countries, leveraging institutional quality measures (Mahmood, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the extent of the magnitude is 0.065 for the 14 EU countries. It, therefore, means that remarkable growth could be achieved in the development of the geothermal energy supply among the 14 EU countries, leveraging institutional quality measures (Mahmood, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…[ 29 ] describes the nonlinear linkage between EGC and ECD. The EKC theory asserts that growth may cause higher emissions at lower income levers and lesser pollution at higher income levels [ 30 ]. This situation can lead to a U-shaped association between income levels and EVD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…During 2010-2019, the average global greenhouse gas emissions (GHGs) reached 54.4 gigatons (GTCO 2 e) due to the utilization of fossil fuel energy and industrialization [2]. According to the United Nations report on climate change, the ambition is to decrease the global temperature to 1.5 • C in 2050 (UNDP, 2015) [3]; however, the continuous increase in environmental degradation issues has gained the attention of many researchers and policymakers working on energy transition.…”
Section: Introductionmentioning
confidence: 99%
“…The environmentally stringent rules and regulations aim to amend individual and organizational behavior in carbon emission (CO 2 ) mitigation by promoting consumption of less-polluting energy [14]. Most scholars have shown that environmentally stringent policy is effective in eliminating carbon dioxide emissions (CO 2 ) [3,[15][16][17] and boosting renewable energy production [18][19][20], but no research has found the effect of the Environmental Policy Stringency Index on energy transition. However, the main purpose of this current research is to analyze the impact of the Environmental Policy Stringency Index, technological innovation, foreign direct investment, and eco-innovation on energy transition in newly industrialized countries.…”
Section: Introductionmentioning
confidence: 99%